Correlating CT findings of stroke with hyperglycemia in acute ischemic stroke patients - Shaker, Ameer (AL-Kindy College Medical Journal, 2019)
Background: Studies show that diabetic patients have a higher incidence of ischemic stroke than non-diabetic patients. In the Framingham study the incidence of thrombotic stroke was 25 times higher in diabetic men and 36 times higher in diabetic women than in those without diabetes Objectives: aim of this study to analyze topography in diabetic patients. Type of study: Cross sectional study. Methods: 48 patients with acute stroke were classified into 4 groups: euglycemic, stress hyperglycemia, newly diagnosed diabetics, and known diabetics. Results:no significant differences were found in the type, site or size of stoke between the 4 groups, higher levels of blood sugars and hemoglobin HbA1cwere significantly higher with chronic white matter ischemia in stroke patients. Conclusions: hyperglycemia, diabetics and chronic glycemic disturbance may play role in the pathophysiology of white matter ischemia.